Power in and over cross-sector partnerships: Actor strategies for shaping collective decisions - Art Dewulf; Willem Elbers (Administrative Sciences, 2018)
While cross-sector partnerships are sometimes depicted as a pragmatic problem solving arrangements devoid of politics and power, they are often characterized by power dynamics. Asymmetries in power can have a range of undesirable consequences as low-power actors may be co-opted, ignored, over-ruled, or excluded by dominant parties. As of yet, there has been relatively little conceptual work on the power strategies that actors in cross-sector partnerships deploy to shape collective decisions to their own advantage. Insights from across the literatures on multiparty collaboration, cross-sector partnerships, interactive governance, collaborative governance, and network governance, are integrated into a theoretical framework for empirically analyzing power sources (resources, discursive legitimacy, authority) and power strategies (power over and power in cross-sector partnerships). Three inter-related claims are central to our argument: (1) the intersection between the issue field addressed in the partnership and an actor's institutional field shape the power sources available to an actor; (2) an actor can mobilize these power sources directly in strategies to achieve power in cross-sector partnerships; and, (3) an actor can also mobilize these power sources indirectly, through setting the rules of the game, to achieve power over partnerships. The framework analytically connects power dynamics to their broader institutional setting and allows for spelling out how sources of power are used in direct and indirect power strategies that steer the course of cross-sector partnerships. The resulting conceptual framework provides the groundwork for pursuing new lines of empirical inquiry into power dynamics in cross-sector partnerships.
Keywords: 350; cross-sector partnerships; institutional fields; issue field; collaboration; power sources; power strategies